Moral hazard problem for poor under joint forest management programme evidence from West Bengal in Indian context - Sarker, Debnarayan (Applied Studies in Agribusiness and Commerce, 2011)
This study explores policy framework on current JFM programme, which secures traditional right of local need subject to the carrying capacity of forest, but face moral hazard problem in which Government cannot legally monitor actions against JFM householdswhich live below poverty line and that extract TFPs for their livelihood, and thereby threatening to sustainability of forest, whereas the incentive work opportunities that Government provides them is insufficient for their subsistence. A good incentive fee dependent on their work plus a lump sum fee (subsidy) are required for their livelihood sustenance and sustainability of forest resources.